فهم منطلقات القصدية وإجراءاتها لتحليل فينومينولوجيا هوسرل - نوال، بلخضر; عطار، أحمد Attar, Ahmed (جامعة وهران 2 محمد بن أحمد - مخبر الأبعاد القيمية للتحولات الفكرية والسياسية, 2018)
إن اليقين والأساس المعرفي من وجهة نظر الفينومينولوجيا نابع من داخل الذات ويقول في هذا المجال "إن التيار الذاتي هو الذي يميز هذه الحقبة من تاريخها ولذلك تطورت في مجالين هما: الاتجاه المتعالي والاتجاه النفسي الأنتربولوجي وقد حاول هوسرل من خلال ذلك التوصل إلى الأساس المعرفي من خلال تأسيس علم جديد للذاتية المتعالية بحيث لا يمكن بدونه أن تصبح الفلسفة علما دقيقا. ولا أن تتحقق بغيره فكرة العالم الكلي اليقيني كما نجد في فينومينولوجيا هوسرل أنه لا تلعب الأبعاد اللغوية والسياسية والأخلاقية دورا تكوينيا فيما يتعلق بتجربة الذات. The phenomenon know Under and to the knowledge of the time of the object of a psychological act which is Most fundamental about which is destined to any eye the nature of the knowledge and can be related to Husserl feel through saying: "The thing does not mean that of this thing, as all the phenomena are formed intentional which directs the perception towards automatically" this characteristic of intentional act of feeling can be detected by the contemplative thought when it reflects the thought on itself of reflect on the conditions of transcendent experiences, and make sure the feeling must be a sense of something according to the intentional act, and this has led to the creation of phenomenological psychology New Its purpose is "the selection systematic models and forms of intentional experience, and its component to its prime objectives as the fixed bottom on which the absolute standard was founded.
Keywords: الفلسفة الأسكلائية -- الوعي الذاتي -- التحليل الماهوي -- هوسرل، إدموند، ت. 1938 م